2018
DOI: 10.1167/iovs.18-24925
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen-Dependent Collagenolytic Properties ofStaphylococcus aureusin Collagen Gel Cultures of Human Corneal Fibroblasts

Abstract: PURPOSE. Staphylococcus aureus is a common cause of corneal ulceration, and staphylokinase (SAK) produced by this bacterium is a plasminogen activator. To investigate the pathogenesis of corneal ulceration induced by S. aureus, we examined the effects of bacterial culture broth and SAK on collagen degradation in a culture model in which human corneal fibroblasts are embedded in a collagen gel. METHODS. Corneal fibroblasts embedded in collagen were exposed to S. aureus culture broth or SAK. Collagen degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In addition, plasminogen is thought to contribute to the pathophysiology of conditions that are associated with the excessive degradation of stromal collagen, such as corneal ulceration, by activating proteolytic enzymes, such as MMPs, secreted from corneal fibroblasts stimulated by IL-1 or bacterial pathogens. 31,32,41 In summary, we showed that plasminogen promotes phagocytic activity of corneal fibroblasts. Although plasminogen has been shown previously to contribute to ECM degradation by corneal fibroblasts under inflammatory conditions, 31,32,39 plasminogen-induced phagocytosis of microparticles did not affect the expression of uPA or MMPs by corneal fibroblasts.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…In addition, plasminogen is thought to contribute to the pathophysiology of conditions that are associated with the excessive degradation of stromal collagen, such as corneal ulceration, by activating proteolytic enzymes, such as MMPs, secreted from corneal fibroblasts stimulated by IL-1 or bacterial pathogens. 31,32,41 In summary, we showed that plasminogen promotes phagocytic activity of corneal fibroblasts. Although plasminogen has been shown previously to contribute to ECM degradation by corneal fibroblasts under inflammatory conditions, 31,32,39 plasminogen-induced phagocytosis of microparticles did not affect the expression of uPA or MMPs by corneal fibroblasts.…”
Section: Discussionmentioning
confidence: 63%
“…31,32,41 In summary, we showed that plasminogen promotes phagocytic activity of corneal fibroblasts. Although plasminogen has been shown previously to contribute to ECM degradation by corneal fibroblasts under inflammatory conditions, 31,32,39 plasminogen-induced phagocytosis of microparticles did not affect the expression of uPA or MMPs by corneal fibroblasts. Plasminogen likely has a regulatory role in the clearance of infectious agents or damaged tissue components by corneal fibroblasts during the early phase of inflammation or wound healing before the arrival of professional phagocytes at corneal stromal lesions.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations